2017
DOI: 10.1159/000485428
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon for Obesity Treatment: Safety, Tolerance, and Efficacy

Abstract: Background: Obesity is an increasing worldwide problem associated with a vast number of comorbidities. Decreasing body weight by only 5-10% has been shown to slow and even prevent the onset of obesity-related comorbidities. Between pharmacological therapy and bariatric surgery a great variety of endoscopic techniques are available, the most common being intragastric balloon (IGB). The purpose of this study was to assess the safety, tolerance, and kinetics of IGBs in weight loss. The kinetics of weight loss wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…However, we have found that after temporary IGB implantation in overweight or obese individuals, a weight loss greater than 10% of baseline weight was achieved in 86.5% of participants. Similar Joana Ribeiro da Silva et al (8) reported the same good results with a smaller number of subjects, of 35.…”
Section: Discussionsupporting
confidence: 70%
“…However, we have found that after temporary IGB implantation in overweight or obese individuals, a weight loss greater than 10% of baseline weight was achieved in 86.5% of participants. Similar Joana Ribeiro da Silva et al (8) reported the same good results with a smaller number of subjects, of 35.…”
Section: Discussionsupporting
confidence: 70%
“…In a similar study, Fernandes et al compared the use of the non-adjustable model alone in overweight and obese patients, showing that %EWL was greater in the overweight patients and %TBWL was greater in the obese patients (32) . Ribeiro da Silva et al obtained similar results; patients with higher BMIs registered the greatest weight losses (33) .…”
Section: Discussionmentioning
confidence: 73%
“…The balloon is left in place for 6 months, then endoscopically removed. The Orbera is the most commonly used IGB in the world, with close to 300,000 devices already distributed (18). A meta-analysis of 17 studies totaling 1,638 patients showed TBWL of 11.3% and EWL of 25.4% at 12 months (19).…”
Section: Orberamentioning
confidence: 99%